Reflection of waves in initially stressed transversely isotropic fibre-reinforced thermoelastic medium - Gupta, Rajani Rani; Gupta, Raj Rani (Zielona Góra: Uniwersytet Zielonogórski)
The present investigation deals with the reflection of plane periodic waves incident at the surface of a homogeneous initially stressed transversely isotropic fibrereinforced thermoelastic medium. The wave equations are solved by imposing proper conditions on displacements, stresses and temperature distribution. Numerically simulated results have been depicted graphically for different angles of incidence with respect to frequency. Some special cases of interest have also been deduced from the present investigation.
Keywords: reflection; initially stressed; fiber-reinforced; transversely isotropic